Unpacking research and practice in world Englishes and Second Language Acquisition. Issue 1 (17th April 2018) - Kubota, Ryuko
Abstract: Research on world Englishes and Second Language Acquisition has conceptualized language, language users, and language learning as diverse and dynamic, broadening conventional knowledge. Yet, research outputs have not influenced language education policies in Expanding Circle countries, which favor Inner Circle standardized English, promote teaching English to young learners, and require monolingual teaching of English, as seen in the case of Japanese primary and secondary education. These activities are perpetuated by macro‐level language ideology and broader political, historical, and economic forces including neoliberalism that exist at a super macro level. Examining the roots of these practices directs our attention to both macro and super‐macro issues as well as to complicities between research/researchers and broader ideological and structural issues. Recommendations are offered to invite researchers to begin exploring how research can make impacts on real‐world issues.